1987
DOI: 10.1079/bjn19870031
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-A-dependent zinc-binding protein and intestinal absorption of Zn in chicks

Abstract: 1. It was demonstrated that the development of experimental avitaminosis A in chicks led to secondary zinc deficiency. The balance of Zn in the chick became negative, while the Zn content of various tissues decreased. Thus in vitamin-A-deficient chicks the serum Zn content was 1258 (SD 26.3) μg/l which was considerably lower than 1652 (SD 97.8) μg/l in controls.2. Zn absorption was considerably reduced throughout the entire small intestine of vitamin-A-deficient chicks and most markedly in the ileal region. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Vitamin A can facilitate Zn absorption via involvement in the synthesis of a protein which binds to Zn at the ileal mucosa. 19 Moreover, it is worthy of note that several studies have shown that the serum retinol concentration is responsive to experimental Zn depletion and repletion. Zn affects many aspects of vitamin A metabolism possibly via involvement in the synthesis of a protein which contributes to inter-and intracellular transport of vitamin A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A can facilitate Zn absorption via involvement in the synthesis of a protein which binds to Zn at the ileal mucosa. 19 Moreover, it is worthy of note that several studies have shown that the serum retinol concentration is responsive to experimental Zn depletion and repletion. Zn affects many aspects of vitamin A metabolism possibly via involvement in the synthesis of a protein which contributes to inter-and intracellular transport of vitamin A.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, vitamin A supplementation has been known to facilitate Zn absorption. 19 In consideration of these difficulties, the present study was aimed to clarify whether high vitamin A supplementation can improve production of the neurotrophins in such communities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Vit. A is necessary for synthesis of a protein which binds to Zn at the ileal mucosa and facilitates its absorption (29). Taken together, it is speculated that change in the daily intake of one or both nutrients may alter the metabolism of the other.…”
Section: Discussionmentioning
confidence: 99%
“…The ice‐cold washed ileum (see above) was cut into 4‐cm segments and used for intestinal preparations. Transport of cadmium or iron through the apical membrane of enterocytes into mucosal cells was estimated by accumulating mucosal preparations (AMPs) . AMPs were incubated at 41 °C for 30 min in 6 ml of one of the following solutions: control buffer (145 mmol·l –1 of NaCl, 4 mmol·l –1 of KCl, 4 mmol·l –1 of Tris‐HCl, 20 mmol·l –1 of fructose, pH 7.4), buffer with 0·05 mmol·l –1 of cadmium (CdCl 2 , Sigma‐Aldrich); buffer with 0·05 mmol·l –1 of L‐AA; buffer with mixture of 0·05 mmol·l –1 of L‐AA and 0·512 mmol·l –1 of iron (AA + Fe1); buffer with mixture of 0·05 mmol·l –1 of L‐AA and 2·56 mmol·l –1 of iron (AA + Fe2).…”
Section: Methodsmentioning
confidence: 99%
“…Transport of cadmium or iron through the apical membrane of enterocytes into mucosal cells was estimated by accumulating mucosal preparations (AMPs). 12 AMPs were incubated at 41 C for 30 min in 6 ml of one of the following solutions: control buffer (145 mmolÁl -1 of NaCl, 4 mmolÁl -1 of KCl, 4 mmolÁl -1 of Tris-HCl, 20 mmolÁl -1 of fructose, pH 7.4), buffer with 0Á05 mmolÁl -1 of cadmium (CdCl 2 , Sigma-Aldrich); buffer with 0Á05 mmolÁl -1 of L-AA; buffer with mixture of 0Á05 mmolÁl -1 of L-AA and 0Á512 mmolÁl -1 of iron (AA + Fe1); buffer with mixture of 0Á05 mmolÁl -1 of L-AA and 2Á56 mmolÁl -1 of iron (AA + Fe2). After incubation, the concentration of Cd or Fe was estimated in AMP by atomic absorption spectrophotometry using a flame AAS (PerkinElmer, model AAnalyst 700.…”
Section: In Vitro Experimentsmentioning
confidence: 99%